Effects of CYP2C19 genetic polymorphisms on the cure rates of H. pylori in patients treated with the proton pump inhibitors: An updated meta-analysis - Zhao, Xianghong; Zhang, Zhongqiu; Lu, Fang; Xiong, Mengqiu; Jiang, Liping; Tang, Ke; Fu, Min; Wu, Yu; He, Bangshun (Frontiers in Pharmacology, 2022)
Background: The cure rates of Helicobacter pylori (H. pylori) treatment using a proton pump inhibitor (PPI) are gradually decreasing due to antibiotic resistance, poor compliance, high gastric acidity, and cytochrome P450 2C19 (CYP2C19) polymorphism, and the effects of PPI depend on metabolic enzymes, cytochrome P450 enzymes. The aim of this meta-analysis was to determine whether CYP2C19 polymorphisms affect H. pylori cure rates in patients treated with different proton pump inhibitors (PPIs) according to stratified analysis. Materials and methods: The literature was searched with the key words “H. pylori” and “CYP2C19” in PubMed, CNKI, and Wanfang up to 31 May 2022, and the studies were limited to clinical observational or randomized controlled trials (RCTs). Finally, seven RCTs and 29 clinical observational studies met the inclusion criteria and were used for the meta-analysis via STATA version 16. Results: The cure rates were significantly different between genotypes of homozygous extensive metabolizers (EM) and poor metabolizers (PM) (OR = 0.58, 95% CI: 0.47–0.71) and between EM and heterozygous extensive metabolizers (IM) (OR = 0.71, 95% CI: 0.59–0.86), but not between IM and PM. Moreover, there was a significantly lower H. pylori cure rate in EM subjects than that in IM subjects when treated with omeprazole (66.4% vs. 84.1%), lansoprazole (76.1% vs. 85.6%), but not rabeprazole, esomeprazole, or pantoprazole. In addition, there was a significantly lower H. pylori cure rate in EM subjects than that in IM subjects when treated with a PPIs for 7 days (77.4% vs. 82.1%), but not 14 days (85.4% vs. 90.0%). Conclusion: Carriers of CYP2C19 loss-of-function variant alleles (IM and PM) exhibit a significantly greater cure rate of H. pylori than noncarriers (EM) regardless of other factors (84.7% vs. 79.2%). In addition, pantoprazole- and rabeprazole-based quadruple therapy for H. pylori treatment is less dependent on the CYP2C19 genotype and should be prioritized in Asian populations with H. pylori.